Phytic acid doped polyaniline porous carbon self-supporting electrode, preparation method thereof and application of phytic acid doped polyaniline porous carbon self-supporting electrode in electrochemical recovery of indium
By introducing porous carbon self -supporting electrodes of polyiline porous carbon self -supporting electrodes, forming compound electrodes rich in phosphate -based groups, solving the problem of limited adsorption capacity and slow dynamic dynamic in existing technology, realized the acidic environment Effective 铟 recycling.
Patent Information
- Application Number
- CN202411685704.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art faces the problems of limited adsorption capacity and slow adsorption kinetics during the recovery process of indium, especially in the acidic environment, which is difficult to effectively recover indium.
The use of porous carbon self -supporting electrodes of polyiline porous carbon is adopted. Through electrochemical recycling methods, the electrical deposition method and proton acid doping technology are used to introduce a functional group rich in phosphate -based groups, which significantly enhances the adsorption capacity of the electrode to the pupae.
The efficient recycling 铟 is achieved in an acidic environment, the adsorption capacity is significantly improved, the adsorption dynamics is accelerated, the operation is simple, the recycling efficiency is high, and it has high selectivity in complex zinc ore tail solution.
Smart Images

Figure CN119372721A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of composite electrode materials and recovery of scattered metal indium, and specifically relates to a phytic acid-doped polyaniline porous carbon self-supporting electrode and a preparation method thereof and application in electrochemical recovery of indium. Background Art
[0002] Indium and its compounds have been widely used in the manufacture of various equipment in the electronics, military and other industries. They play a key role in ensuring national defense and economic security, and determine the level of national industrialization and modernization. Therefore, the European Commission has listed indium as a key strategic metal. For example, indium has become a key material in the fields of optical fiber communications and solar cells due to its conductivity and transparency. The market demand for indium is showing a rapid growth trend. However, the content of indium in the earth's crust is about 10 -4 %, and no independent indium deposits have been found so far. Most of them are associated with sulfide ores of non-ferrous metals such as zinc. Therefore, developing an efficient method for recovering indium is of great significance to ensure the long-term sustainable supply of strategic metal indium.
[0003] Adsorption has become the preferred method for recovering indium because it is safe, environmentally friendly and easy to operate. However, traditional adsorbents often face the challenges of limited adsorption capacity and slow adsorption kinetics. Researchers have found that applying a certain potential during the adsorption process can induce the formation of a double layer at the interface between the electrode and the solution that can store charged particles. This not only significantly improves the adsorption capacity of the adsorbent, but also accelerates the migration of ions to the adsorbent surface, thereby greatly shortening the adsorption time.
[0004] Polyaniline (PANI) is the best choice for electrosorption materials due to its cost-effectiveness, acid and alkali resistance, and extremely high theoretical specific capacitance. However, the adsorption capacity and selectivity are usually unsatisfactory when relying solely on capacitive adsorption. To solve the above problems, specific functional groups can be introduced into polyaniline by proton acid doping to increase additional adsorption sites. The researchers found that the phosphate group showed a strong affinity for trivalent indium and became a key functional group to enhance the adsorption effect. Based on this discovery, a phytic acid-doped polyaniline porous carbon self-supporting electrode (PA-PANI / PC) was successfully prepared using phytic acid rich in phosphate groups by a simple and rapid electrochemical polymerization method. The prepared composite electrode not only retains the original advantages of polyaniline and nitrogen-containing porous carbon, but also significantly improves its adsorption capacity for indium by introducing phosphate groups. In addition, the composite electrode achieves efficient recovery of indium and simplifies the operation process through an electrochemical recovery process, providing a new technical path for the recovery of indium. Summary of the invention
[0005] The present invention mainly aims at the problem of recovering indium in an acidic environment, develops and designs a self-supporting electrode, and adopts an electrochemical recovery method to achieve efficient separation and recovery of indium. The polyaniline is quickly attached to the porous carbon-modified carbon cloth within 5-15 minutes by electrodeposition, and phytic acid rich in phosphate groups is introduced by proton acid doping. The method of electrochemical recovery of indium involved in the present invention is not only simple to operate and can quickly complete the adsorption process, but also has high recovery efficiency and can stably operate in an acidic environment, so it has high practical utilization value.
[0006] The present invention is realized by the following technical scheme: the phytic acid doped polyaniline porous carbon self-supporting electrode is prepared by using the electrodeposition method to induce aniline polymerization on the carbon cloth coated with porous carbon, and at the same time, phytic acid is combined with polyaniline to introduce specific adsorption sites to prepare the composite electrode PA-PANI / PC.
[0007] The above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode comprises the following steps:
[0008] 1) Dissolve zinc nitrate hexahydrate and 2-methylimidazole in methanol respectively, and dissolve them by ultrasound;
[0009] 2) mixing the two solutions obtained in step 1), stirring at room temperature, and then subjecting to aging treatment;
[0010] 3) centrifuging the solution obtained in step 2), washing with methanol and drying to obtain white crystalline ZIF-8;
[0011] 4) placing the ZIF-8 obtained in step 3) in a tube furnace for pyrolysis, washing with dilute hydrochloric acid and deionized water after pyrolysis, and drying to obtain a black powder, namely nitrogen-containing porous carbon (PC);
[0012] 5) mixing the PC obtained in step 4) with carbon powder and polyvinylidene fluoride in a certain mass ratio into a slurry, coating the slurry on the acid-treated carbon cloth, and drying the slurry to obtain a PC carbon cloth electrode;
[0013] 6) constructing a three-electrode system, with the PC carbon cloth electrode obtained in step 5) as the working electrode, the silver / silver chloride electrode as the reference electrode, the platinum sheet electrode as the auxiliary electrode, and the electrolyte being a mixed solution of phytic acid and aniline monomers;
[0014] 7) Apply a certain voltage to the three-electrode system constructed in step 6) to obtain a PA-PANI / PC electrode, wash it with deionized water, and dry it.
[0015] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 1), the amount of zinc nitrate hexahydrate used is 2.68 g, and the amount of 2-methylimidazole used is 0.66 g.
[0016] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, the amount of methanol used in step 1) is 100 mL.
[0017] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, the stirring time in step 2) is 1-3 hours, and the aging time is 12-48 hours.
[0018] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 3), the drying temperature is 60-80° C. and the drying time is 12 hours.
[0019] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, the pyrolysis temperature in step 4) is 800-1000°C, and the heating rate is 5°C·min -1 , the pyrolysis time is 2-3h.
[0020] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, the concentration of the dilute hydrochloric acid in step 4) is 1 mol·L -1 .
[0021] Furthermore, in the above method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, the drying temperature in step 4) is 60-80°C.
[0022] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 5), the total mass of PC, carbon powder and polyvinylidene fluoride is 20 mg.
[0023] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 5), the mixed slurry is mixed in a mass ratio of PC: carbon powder: polyvinylidene fluoride = 8:1:1.
[0024] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 5), the drying temperature is 60-80° C. and the drying time is 12 hours.
[0025] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 6), the molar ratios of phytic acid and aniline in the mixed solution are 1:1, 1.5:1, 2:1, 3:1, and 6:1, respectively.
[0026] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, in step 7), the voltage is 0.8-1.2 V and the time is 5-15 min.
[0027] Furthermore, in the above-mentioned method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode, the drying temperature in step 7) is 60-80°C.
[0028] The above-mentioned phytic acid-doped polyaniline porous carbon self-supporting electrode is used for electrochemical recovery of indium.
[0029] Furthermore, the above application method is as follows: in an indium-containing solution, PA-PANI / PC is used as a cathode and a carbon rod is used as an anode, the voltage is 0-1.2V, and the power is applied for 2-3h at room temperature.
[0030] Furthermore, in the above application, the pH of the indium-containing solution is 1.0-4.0 and the concentration is 50-400 mg·L -1 .
[0031] The beneficial effects of the present invention are:
[0032] 1. The composite electrode prepared by the present invention introduces phytic acid into polyaniline, which ensures high capacitance of the electrode while providing abundant adsorption sites, improves the acid resistance and hydrophilicity of the composite electrode, and increases the possibility of its application in actual acidic mineral fluids.
[0033] 2. In the present invention, PA-PANI / PC-2 has high adsorption capacity and fast adsorption kinetics, that is, the adsorption capacity is as high as 284.67 mg·g at pH 2.5. -1 , the equilibrium time is 60 minutes, and most of the indium can be recovered in the first 20 minutes.
[0034] 3. The composite electrode prepared by the present invention can recover indium with high selectivity in a complex system simulating zinc ore tailings.
[0035] 4. The composite electrode prepared by the present invention can recover indium in the form of precipitation, avoiding an additional backwashing process, simplifying the operation process, and having certain practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the infrared spectrum of PA-PANI / PC-2 prepared in Example 3.
[0037] Figure 2 This is the water contact angle test of PA-PANI / PC-2 prepared in Example 3.
[0038] Figure 3 The phytic acid-doped polyaniline porous carbon self-supporting electrodes prepared in Examples 2-4 with different molar ratios of phytic acid and aniline were tested at 1 A·g -1 Charge and discharge test curve under current density.
[0039] Figure 4The indium extraction capacity of PC prepared in Example 1, PA-PANI / PC-2 prepared in Example 3, and HCl-PANI / PC prepared in Example 7.
[0040] Figure 5 The recovery efficiency of indium by the phytic acid-doped polyaniline porous carbon self-supporting electrode PA-PANI / PC with different molar ratios of phytic acid and aniline prepared in Examples 2-4.
[0041] Figure 6 The recovery efficiency of indium by PA-PANI / PC-2 prepared in Example 3 at different pH values.
[0042] Figure 7 The extraction capacity / recovery efficiency of indium of PA-PANI / PC-2 prepared in Example 3 at different voltages.
[0043] Figure 8 The saturation adsorption curves of PA-PANI / PC-2 prepared in Example 3 at different indium concentrations.
[0044] Fig. 9 The distribution coefficient of the adsorption of different metal ions in the simulated indium-rich zinc ore solution by PA-PANI / PC-2 prepared in Example 3.
[0045] Fig.10 The cyclic electrochemical recovery efficiency of indium by PA-PANI / PC-2 prepared in Example 3. Specific implementation methods
[0047] Example 1 Nitrogen-containing porous carbon self-supporting electrode
[0048] (1) Accurately weigh 2.68 g zinc nitrate hexahydrate and 0.66 g 2-methylimidazole and dissolve them in 100 mL methanol solution. Ultrasonic treatment is used to fully dissolve them. The two solutions are then mixed, stirred at room temperature for 1 h, and aged for 12 h. The aged solution is centrifuged to obtain white solid ZIF-8, which is washed with methanol three times and dried at 60-80 °C for 12 h. The prepared ZIF-8 is pyrolyzed at 900 °C for 2 h, with a heating rate of 5 °C min -1 After the pyrolysis is completed, 1 mol·L -1 The product was washed with HCl and deionized water three times respectively and dried at 60°C to obtain a black powder, namely nitrogen-containing porous carbon (PC).
[0049] (2) PC, carbon powder and polyvinylidene fluoride were mixed by ultrasonic at a mass ratio of 8:1:1 (total mass 20 mg). After being fully mixed, the mixed slurry was evenly coated on the acid-pretreated carbon cloth and dried at 60°C for 12 h to obtain a PC self-supporting electrode.
[0050] Example 2 Phytic acid doped polyaniline porous carbon self-supporting electrode (PA-PANI / PC-1)
[0051] A three-electrode system was constructed with the PC self-supporting electrode prepared in Example 1 as the working electrode, the silver / silver chloride electrode as the reference electrode, and the platinum sheet electrode as the auxiliary electrode. 0.72 g of distilled aniline and 5.28 g of 50% phytic acid were prepared into an electrolyte solution. Electrodeposition was performed at 0.9 V for 5 min. After the deposition, the working electrode was rinsed three times with deionized water and dried at 60° C. overnight to obtain PA-PANI / PC-1.
[0052] Example 3 Phytic acid doped polyaniline porous carbon self-supporting electrode (PA-PANI / PC-2)
[0053] Referring to the steps in Example 2, the masses of aniline and phytic acid were controlled to be 0.72 g and 7.92 g, respectively, to prepare a phytic acid-doped polyaniline porous carbon self-supporting electrode, namely, PA-PANI / PC-2.
[0054] Example 4 Phytic acid doped polyaniline porous carbon self-supporting electrode (PA-PANI / PC-3)
[0055] Referring to the steps in Example 2, the masses of aniline and phytic acid were controlled to be 0.72 g and 10.56 g, respectively, to prepare a phytic acid-doped polyaniline porous carbon self-supporting electrode, namely, PA-PANI / PC-3.
[0056] Example 5 Phytic acid doped polyaniline porous carbon self-supporting electrode (PA-PANI / PC-4)
[0057] Referring to the steps in Example 2, the masses of aniline and phytic acid were controlled to be 0.36 g and 7.92 g, respectively, to prepare a phytic acid-doped polyaniline porous carbon self-supporting electrode, namely, PA-PANI / PC-4.
[0058] Example 6 Phytic acid doped polyaniline porous carbon self-supporting electrode (PA-PANI / PC-5)
[0059] Referring to the steps in Example 2, the masses of aniline and phytic acid were controlled to be 0.18 g and 7.92 g, respectively, to prepare a phytic acid-doped polyaniline porous carbon self-supporting electrode, namely, PA-PANI / PC-5.
[0060] Example 7 Hydrochloric acid doped polyaniline porous carbon self-supporting electrode
[0061] Referring to the steps in Example 2, the mixed solution of aniline and phytic acid was replaced with an equivalent volume of a mixed solution of aniline and hydrochloric acid, wherein the concentration of hydrochloric acid was 1 mol·L -1 , that is, a porous carbon self-supporting electrode HCl-PANI / PC doped with hydrochloric acid is obtained.
[0062] Example 8 Characterization of Phytic Acid Doped Polyaniline Porous Carbon Self-Supporting Electrode
[0063] The composite electrode prepared in Example 3 was subjected to infrared spectroscopy, water contact angle test, and constant current charge and discharge test. Figure 1 , Figure 2 and Figure 3 shown. Figure 1 In the infrared spectrum, the -1 The two sharp peaks at 1148 and 1050 cm-1 are attributed to the stretching vibration of the quinone ring and the benzene-like ring in polyaniline. -1 The peaks are attributed to the fine structure of the phosphate group, and the appearance of these peaks indicates that phytic acid-doped polyaniline was successfully synthesized by electrodeposition. Figure 2 The water contact angle images of the blank electrode and the composite electrode prepared in Example 3 are shown in Figure 1. It can be seen from the figure that the addition of phytic acid and polyaniline greatly improves the hydrophilicity of the electrode, helps to improve the accessibility of indium ions and promotes complexation. The results of the constant current charge and discharge experiment are shown in Figure 2. Figure 3 The asymmetric triangle curve shows that the electrodes have pseudocapacitance, among which the PA-PANI / PC-2 electrode has the largest specific capacitance, which can reach 238 F·g -1 .
[0064] Example 9: Recovery experiment of indium using different porous carbon self-supporting electrodes
[0065] Methods: A two-electrode system was constructed with the prepared composite electrode as cathode and carbon rod as anode. -1 , a voltage of 1.2 V was applied to an indium solution with a pH of 2.5 and the power was turned on for 2.5 h. The composite electrodes were respectively the porous carbon self-supporting electrode PC prepared in Example 1, the phytic acid-doped polyaniline porous carbon self-supporting electrode PA-PANI / PC-2 prepared in Example 3, and the hydrochloric acid-doped polyaniline porous carbon electrode HCl-PANI / PC prepared in Example 7.
[0066] from Figure 4 It can be seen that the extraction capacity of PA-PANI / PC-2 is significantly higher than that of HCl-PANI / PC and PC, and the carbon cloth electrode coated with PC alone has almost no adsorption effect on indium. This is because the conductivity of polyaniline brings about capacitive adsorption, and the abundant phosphate groups on the surface of phytic acid molecules have a strong coordination effect with indium, which effectively promotes the capture of target ions.
[0067] Example 10 Experimental recovery of indium using polyaniline porous carbon self-supporting electrodes doped with phytic acid at different molar ratios
[0068] Method: Referring to Example 9, PA-PANI / PC-1, PA-PANI / PC-2, and PA-PANI / PC-3 were used as cathodes and carbon rods were used as anodes to build a two-electrode system for electrochemical recovery experiments. The cathode was controlled to be a composite electrode prepared with different molar ratios of phytic acid and aniline.
[0069] from Figure 5 It can be found that with the increase of phytic acid doping amount, the recovery efficiency of indium shows a trend of first increasing and then decreasing. The reason is that too much phytic acid will cause the stacking of phosphate active groups, hindering its combination with indium; conversely, too little phytic acid content will result in fewer phosphate active groups and unsaturated adsorption sites, thereby reducing the recovery efficiency.
[0070] Example 11 Experimental recovery of indium by phytic acid-doped polyaniline porous carbon self-supporting electrode at different acidities
[0071] Method: Referring to Example 9, the PA-PANI / PC-2 prepared in Example 3 was used as the cathode and the carbon rod was used as the anode to build a two-electrode system for electrochemical recovery experiments, and the pH value of the indium-containing solution was controlled in the range of 1.0-4.0.
[0072] from Figure 6 It can be seen that the recovery efficiency increases with the increase of pH. In a highly acidic environment, the phosphate groups on the electrode surface are easily protonated, resulting in hydrogen ions occupying the adsorption sites. The competitive adsorption is significantly enhanced, resulting in a low recovery efficiency of indium. As the pH increases, the degree of competitive adsorption decreases, and more adsorption sites are combined with indium. At the same time, when the pH increases further, the indium ions will hydrolyze to promote separation. Considering the actual environment of the highly acidic zinc ore tailings, pH 2.5 was selected as the optimal acidity for subsequent indium recovery experiments.
[0073] Example 12 Indium recovery experiment of phytic acid-doped polyaniline porous carbon self-supporting electrode at different voltages
[0074] Method: Referring to Example 9, the PA-PANI / PC-2 prepared in Example 3 was used as the cathode and the carbon rod was used as the anode to build a two-electrode system for electrochemical recovery experiments. The applied voltage was controlled to be 0, 0.8, 0.9, 1.0, and 1.2 V, respectively, and the adsorption time was 120 min.
[0075] exist Figure 7 It can be observed that when the external potential is 1.2V, the adsorption efficiency of indium reaches the maximum, and its value is 3.3 times that when there is no voltage. This shows that the increase in voltage provides greater power for ion transport during the adsorption process. Therefore, electrochemical technology can effectively enhance the material's adsorption capacity for indium.
[0076] Example 13 Recovery experiment of phytic acid-doped polyaniline porous carbon self-supporting electrode at different indium concentrations
[0077] Method: Referring to Example 9, PA-PANI / PC-2 prepared in Example 3 was used as cathode and carbon rod as anode to build a two-electrode system for electrochemical recovery experiment. The initial concentration of indium solution was controlled to be 50, 80, 100, 200, 300, 400 mg·L -1 During the adsorption process, samples were taken at different time points and the concentration of indium before and after adsorption was determined by atomic absorption spectroscopy. Figure 8 It was found that the saturated adsorption capacity of indium on PA-PANI / PC-2 could reach 284.67 mg·g -1 , equilibrium can be reached within 60 minutes, and most of the recovery work can be completed in the first 20 minutes.
[0078] Example 14 Experimental study on the selectivity of phytic acid-doped polyaniline porous carbon self-supporting electrode for indium recovery
[0079] Method: Referring to Example 9, PA-PANI / PC-2 prepared in Example 3 was used as the cathode and the carbon rod was used as the anode to build a two-electrode system for electrochemical recovery experiments. The electrolyte was controlled to be a simulated zinc ore solution. The simulated zinc ore solution containing indium was prepared according to the concentration ratio of each metal ion, that is, the concentration ratio of In(Ⅲ):Fe(Ⅱ):Al(Ⅲ):Zn(Ⅱ):Mg(Ⅱ):Ca(Ⅱ) was 1:1.5:5:30:0.6:0.7. The pH of the simulated solution was 2.5, the applied voltage was 1.2V, and the adsorption was 60min. The distribution coefficient K was calculated. d .
[0080] from Fig. 9 It can be found that the removal rates are In(Ⅲ)>Al(Ⅲ)>Ca(Ⅱ)>Mg(Ⅱ)>Fe(Ⅱ)>Zn(Ⅱ), among which the distribution coefficient K of In(Ⅲ) is d About 4000mL·g -1 , indicating that PA-PANI / PC-2 has a high selectivity for indium and can separate indium from complex feed solutions.
[0081] Example 15 Cyclic performance experiment of phytic acid-doped polyaniline porous carbon self-supporting electrode
[0082] Method: After washing and drying the PA-PANI / PC-2 adsorbed in Example 3, add 50 mL of 0.12 mol·L -1 The electrodeposition was carried out at 0.9 V for 5 min in a phytic acid solution, and then the electrode was rinsed with deionized water and dried to obtain a new composite electrode PA-PANI / PC-2. The electrochemical recovery experiment was carried out according to Example 9.
[0083] After seven repeated electrochemical recovery experiments, the recovery efficiency can still be maintained at 78%, indicating that the composite electrode has good stability and repeatability.
Claims
1. A phytic acid-doped polyaniline porous carbon self-supporting electrode, characterized in that: The composite electrode PA-PANI / PC was prepared by modifying phytic acid and polyaniline on porous carbon using electrodeposition.
2. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 1, characterized in that: The steps include: 1) placing ZIF-8 in a tube furnace for pyrolysis, washing with dilute hydrochloric acid and deionized water after pyrolysis, and drying to obtain a black powder, namely nitrogen-containing porous carbon PC; 2) mixing the PC obtained in step 1) with carbon powder and polyvinylidene fluoride according to a mass ratio, coating the mixture on an acid-treated carbon cloth, and drying the mixture to obtain a PC carbon cloth electrode; 3) The PC carbon cloth electrode obtained in step 2) is used as the working electrode, the silver / silver chloride electrode is used as the reference electrode, the platinum sheet electrode is used as the auxiliary electrode, and the electrolyte is a mixed solution of phytic acid and aniline monomers, and an external voltage is applied by turning on the power supply; 4) After applying power for a period of time, the PA-PANI / PC electrode is obtained, which is washed with deionized water and dried.
3. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 2, characterized in that: In step 1), the preparation method of ZIF-8 is as follows: zinc nitrate hexahydrate and 2-methylimidazole are dissolved in methanol respectively, the two solutions are mixed, stirred at room temperature and aged to obtain a white precipitate ZIF-8.
4. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 3, characterized in that: The stirring time is 1-3 hours and the aging time is 12-48 hours.
5. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 2, characterized in that: In step 1), the pyrolysis temperature is 800-1000°C, and the heating rate is 5°C·min -1 , the pyrolysis time is 1-3h.
6. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 2, characterized in that: In step 3), the external voltage is 0.8-1.2V.
7. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 2, characterized in that: In step 3), the molar ratio of phytic acid to aniline in the mixed solution is 1:1 to 6:
1.
8. The method for preparing a phytic acid-doped polyaniline porous carbon self-supporting electrode according to claim 2, characterized in that: In step 4), the power-on time is 5-15 minutes.
9. Application of a phytic acid-doped polyaniline porous carbon self-supporting electrode in electrochemical recovery of indium as claimed in claim 1, characterized in that: In an indium-containing solution, PA-PANI / PC is used as the cathode and the carbon rod is used as the anode. The voltage is 0-1.2V and the power is applied for 2-3h at room temperature.
10. The use of a phytic acid-doped polyaniline porous carbon self-supporting electrode in electrochemical recovery of indium according to claim 1, characterized in that: The pH of the indium solution is 1.0-4.0 and the concentration is 50-400 mg·L -1 .
Citation Information
Cited By
Preparation method of phosphoric acid doped polypyrrole electrode material and application of phosphoric acid doped polypyrrole electrode material in electrochemical adsorption recovery of indium in LCD pickle liquor
CN120573815A